Substantive analysis of value competencies of future teachers of fine arts (Pedagogy of Higher and Secondary Education, 2009)
The article offers contentual analysis of future art teachers‘ value competencies. The analysis of notions competencies and competence is given.
Keywords: competence; jurisdictions; valued jurisdictions